PERENCANAAN STRUKTUR ULANG GEDUNG BADAN PEMBERDAYAAN MASYARAKAT DAN NAGARI KABUPATEN PASAMAN BARAT - Candra, Iseng; Eka Priana, Surya; Bastian, Elfania (Jurnal Riset Multidisiplin Agrisosco, 2023)
Building Planning The Community Empowerment Agency and Nagari is one of the government buildings, the planned building is a 3-storey office building located in the West Pasaman earthquake area. so planning is needed that leads to being resistant to earthquake shocks, this is one of the basics for planners to plan the Community and Nagari Empowerment Agency Building. From the results of this structural analysis, the reinforcement structure is obtained based on the author's analysis. The results obtained that the material used is steel fy = 420 MPa and concrete quality fc' = 24.9 MPa, for plate reinforcement in the direction of x = 10 – 150, while the direction of y = 10 – 150. Column planning uses quality fy = 420 and concrete quality fc' = 24.9 Mpa for a 40cm x 40cm column with the main reinforcement used, namely 8D – 16 and a 30cm x 30cm column with the main reinforcement used 6D – 16. While the beam design uses steel quality fy = 420 Mpa and muru concrete fc' = 24.9 MPa for beams measuring 50cm x 30cm with reinforcement used 6D – 16 16 for tensile reinforcement and 3D – 16 for compression reinforcement, steel quality fy = 420 and concrete quality fc' = 20.75 for beam size 45cm x 25cm with reinforcement used 4D – 13 for tensile reinforcement and 3D – 13 for compression reinforcement, while for beams using steel quality fy = 400 and quality beron fc' = 20.75 for size 30cm x 20cm with the main reinforcement used 3D – 12 for tensile reinforcement and 2D – 12 for compression reinforcement.reinforcement.